Can Time–Space Compression Promote Urban Economic Growth? Evidence from China's High‐speed Rail Projects. Issue 5 (30th September 2020) - Yao, Shujie; Fang, Jing; He, Hongbo
Abstract: This paper studies the effect of high‐speed rail (HSR) on urban economic growth using a panel data comprising 285 Chinese cities in 2007–2017. Combining the endogenous growth model with a difference‐in‐difference analysis, we extend the horse‐mass theory to explain how China may use HSR to avoid the so‐called middle‐income trap. The paper also examines the efficient boundaries of HSR and simultaneously studies HSR time–space compression as well as the city neighboring effects on economic growth. It is found that HSR's efficient boundaries are within the range of 200–1, 200 km for provincial capitals and 50–300 km for prefecture‐level cities. HSR stimulates economic growth by approximately 0.6 percent, and the neighboring effect accounts for one‐quarter of economic growth. Three policy implications are drawn: (i) China needs to further reduce the travel times between the inland provincial cities and Beijing, Shanghai or Guangzhou; (ii) China should build a denser HSR network to maximize its economic impact on the vast majority of cities; (iii) China needs to develop some powerful economic growth centers in the inland areas to lead the development of their neighboring cities.